The Dock Construction of Inter-Island in Indonesia - Mohamad Fajrunnajah (POLITEKNIK NEGERI JAKARTA, 2020)
Sea transportation is important to support economic wheels and equitable distribution in inter-island areas in Indonesia. Therefore, adequate transportation facilities and infrastructure need to be provided. With the availability of docks, transportation of goods, services or human transportation can be easier and more efficient. In addition, Indonesia's pulai coast has become a tourist attraction. The types of docks in Indonesia are adapted to the facilities and needs of berths and their functions for the island community. The pier construction is planned to use the method of analyzing the data according to the water, seismic data, wind data, the availability of local materials, size and layout planning and structural planning. The purpose of this study is to find out the general shape of the interisland pier structure in Indonesia. The method used in this study is a literature review on the interisland pier in Indonesia. The results of the literature review indicate that there are three forms of pier structure in Indonesia with the most form being the quay form which is dominated by the transportation functions of loading and unloading trade goods, and the form of jetty which is dominated by the human transportation function. The shape of the jetty is generally not only made from concrete foundations and deck plates but also uses local materials.